Morphological Analysis of Shortened Forms on Instagram as a Source for Learning Indonesian - Verlin, Sri (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
Social media platforms like Instagram encourage word shortening and other non-standard vocabulary developments. This phenomenon is typically overlooked in Indonesian language morphology instructional materials, which emphasize normative principles. Therefore, an in-depth morphological analysis of these shortening forms and an exploration of their potential as authentic learning resources are needed. Therefore, this study aims to (1) identify and classify the dominant types of word shortening on Instagram, (2) analyze the morphological process of forming these shortening forms, and (3) formulate didactic implications for utilizing these findings as a source for learning Indonesian language morphology. This study uses a qualitative descriptive approach with a content analysis method. Data in the form of text (captions, comments, and stories) containing shortened forms were collected from Indonesian-language Instagram accounts and analyzed based on morphological rules. The results show that abbreviations and contractions are the most dominant types of shortening on Instagram. The most active morphological processes are syllable fragmentation (apocope) and vowel deletion (syncope). The analysis shows that although many shortened forms are nonstandard, their formation patterns still follow principles of lexical efficiency that can be explained morphologically. This study makes a significant contribution by offering a contextualized morphology teaching model based on contemporary language practices. Utilizing Instagram data can increase student learning interest and bridge the gap between language theory in the classroom and the reality of everyday digital communication.